Energy Levels in Pt192 and Pt194 - MacArthur, John Duncan (My University, 1962)
The technique of recording coincidence events has been applied in the study of several nuclei. Two platinum nuclides have been investigated experimentally through the use of two types of coincidence spectrometers. For both these nuclei, Pt^192 and Pt^194, the investigation included beta-gamma experiments which measured the intensities of the beta groups feeding some of the levels in these nuclei and directional correlation experiments which determined the spins of some of their excited states. A study of the gamma-gamma coincidences of Pt^194 confirmed the decay scheme proposed by previous workers. The directional correlation of the one cascade in Co^58 forms the part of the paper present in Chapter IV. Finally, the appendices contain a description of an apparatus for the preparation of beta sources and an explanation of a set of experiments designed to calibrate the gamma-gamma coincidence spectrometer for its tasks.
Keywords: energy, levels, nuclei, platinum, coincidence, beta